TRANSFORMASI TUJUAN PENDIDIKAN NASIONAL PERSPEKTIF PENDIDIKAN ISLAM - Ah Zakki Fuad; Jauharoti Alfin (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
The objectives of national education in Indonesia as stipulated in the law of the Republic of Indonesia are transformed from the old order, the new order, the reformation order until the issuance of the National Education System Law Number 20 of 2003. The transformation of national education objectives is caused by several things; socio-political situation, class interests, parliamentary power and so on. On the other hand had Islamic education designs and concepts of its own in formulating educational objectives that are derived from the Qur'an. The second formulation of the educational objectives of this same same has significance in the learning activities in the institution. It is therefore important to know how the purpose of national education Indonesia prespective Islamic education.